Determinants of technical efficiency in the ASEAN manufacturing industry - Hiong, Jee Kouk; Ab-Rahim, Rossazana (Asian Journal of Economic Modelling, 2025)
This study investigates the determinants of technical efficiency in the manufacturing sector across six ASEAN economies Indonesia, Malaysia, the Philippines, Singapore, Thailand, and Vietnam over the period 2000–2022. The purpose is to assess cross-country variations in efficiency performance and identify key macroeconomic and demographic drivers that shape long-term productivity. The analysis adopts a two-stage framework that combines Data Envelopment Analysis (DEA) with Tobit regression. The DEA results reveal substantial heterogeneity, with Singapore consistently achieving the highest efficiency, while Vietnam persistently lagged behind. Although an overall upward trend is observed, efficiency in Indonesia, Thailand, and Vietnam declined notably after the COVID-19 pandemic, reflecting the sector’s vulnerability to external shocks. The Tobit regression results show that foreign direct investment (FDI) is a significant positive determinant, with a 1% increase in FDI inflows enhancing efficiency by 0.44%. In contrast, macroeconomic instability and demographic pressures undermine performance, as a 1% rise in inflation reduces efficiency by 1.14%, and a 1% increase in the elderly population share decreases efficiency by 2.88%. These findings highlight the importance of policies that promote sustained FDI inflows, stabilize inflation, and address aging through labor market reforms and productivity-enhancing measures. Strengthening manufacturing efficiency is essential for sustaining long-term growth, boosting global competitiveness, and advancing ASEAN’s regional integration agenda.